Political Science B.A. Graduates from the University of Calgary: Education and Career Paths - Archer, Keith (Canadian Journal of Higher Education, 1986)
A mailed questionnaire was administered to 199 graduates of the B.A. programme in political science between 1967 and 1985. It was found that (a) most graduates (63%) continued studies after graduation, although the proportion who did so increased as rates of unemployment increased; (b) the most popular occupations among graduates were lawyer (22.2%), manager or consultant (17%), teacher (14.8%) and civil servant (14.8%), with males more likely than females to be employed in each of these except law; (c) of the four most popular occupations, two (teacher and civil servant) are becoming closed to graduates with cutbacks in the growth of public sector spending; and (d) that the graduate of the 1980s is much more flexible both during and after university than were previous graduates. These findings are discussed with reference to the changing employment prospects for political science graduates.